Circularity in the construction and demolition industry: Comparing weighting methods for multi-criteria decision analysis - Dytianquin, Norman; Kalogeras, Nikos; van Oorschot, John; Abujidi, Nurhan (Frontiers in Sustainability, 2023)
In studying circularity in the construction and demolition industry (CDI) in the EU, five projects in selected EU countries were compared to assess how the application of circularity achieved balance in the environment, social and economic dimensions of sustainability. The selected projects using secondary data based on a web search of these projects involved different stages of the circularity ladder, used diverse design principles, and focused on different stages of the construction life cycle, making them interesting comparators for applying circularity in CDI. For strong sustainability to exist, there should be a balance between the sustainability triptych covering environment, social and economic dimensions which is often overlooked in many circular and sustainability projects with an overemphasis on one dimension and disregard for another. Selected indicators for the three dimensions included those found in environmental impact and life cycle assessments for environmental criteria, social impact assessments for social criteria and economic feasibility, and project appraisal and evaluation reports for economic criteria. In weighting criteria, several methods exist comprising subjective, objective, and integrated techniques. The robustness of objective vs. subjective weights is rather debatable. The objective of the research is to test different weighting techniques using subjective and objective methods to determine if differences in project rankings exist in terms of sustainability balance. The ranking of projects and conclusions about best practices in the CDI circular economy could be influenced by the weighting techniques used. As the weighting of criteria could influence project outcomes, objectivity in weighting is often advised. However, in this study, computational comparisons indicated that subjective methods do not significantly differ from objective ones that use mathematical and statistical rigor. As such, subjective weighting methods still conveniently capture credible and consistent results. Nonetheless, this should not detract from efforts to objectify weighting methods that lend more credence and justification to scoring and ranking results.